1
$\begingroup$

Let $f: \mathbb R \to \mathbb R$ be a non constant continuous function such that $(e^x-1)f(2x)= (e^{2x}-1)f(x)$. If $f'(0) =1 $, then $\lim_{x\to 0}\left(\dfrac {f(x)}{x}\right)^{\frac 1x}= ? $

I am trying hard to find $f(x)$ but unable to.

Attempt:

Differentiating both sides of the equation and putting $x=0$, we obtain $f(0)= 0$.

After that can we directly substitute f(x)= exact $0$ and say that limit doesn't exist (which is not the answer)?

How do I go about solving it?

The answer is:

$e^{\frac12}$

$\endgroup$
  • $\begingroup$ A quick look tells me that $f(x)=e^x-1$. I don't know if that is the only possibility for $f$ $\endgroup$ – randomgirl Jun 9 '18 at 16:28
  • $\begingroup$ Pretending that is the only $f$.... you should get your spoiler you posted. $\endgroup$ – randomgirl Jun 9 '18 at 16:42
  • $\begingroup$ @randomgirl how? $\endgroup$ – Archer Jun 9 '18 at 16:49
  • $\begingroup$ m.wolframalpha.com/input/… $\endgroup$ – randomgirl Jun 9 '18 at 16:53
  • $\begingroup$ @randomgirl I wanted to know the method instead $\endgroup$ – Archer Jun 9 '18 at 16:54
3
$\begingroup$

Let us prove that $f(x) = e^x-1$ is the unique function satisfying the given conditions.

Namely, as already observed, differentiating the functional equation and evaluating at $x=0$ gives $f(0) = 0$.

Let us consider the function $g(x) := f(x) / (e^x - 1)$, $x\neq 0$. Since $f(0) = 0$ and $f'(0) = 1$, there exists the limit $$ \lim_{x\to 0} \frac{f(x)}{e^x -1} = \lim_{x\to 0} \frac{f(x)}{x}\cdot\frac{x}{e^x-1} = f'(0) = 1, $$ so that $g$ can be continuously extended to all $\mathbb{R}$ by setting $g(0) = 1$.

Hence, $g$ is a continuous function satisfying $$ g(0) = 1, \qquad g(2x) = g(x), \quad \forall x\in\mathbb{R}. $$ But the only continuous function satisfying these conditions is the constant function $g \equiv 1$, i.e., $f(x) = e^x - 1$.

Namely, given $x\neq 0$ it holds $$ g(x) = g\left( \frac{x}{2^n}\right), \qquad \forall n\in\mathbb{N}, $$ hence $$ g(x) = \lim_{n\to +\infty} g\left( \frac{x}{2^n}\right) = g(0) = 1. $$

Now the computation of the required limit is easy: $$ \lim_{x\to 0} \left(\frac{f(x)}{x}\right)^{1/x} = \lim_{x\to 0} \exp\left[\frac{1}{x}\log\left(\frac{e^x-1}{x}\right)\right] = \lim_{x\to 0} \exp\left[\frac{1}{x}\log\left(1+\frac{x}{2}\right)\right] = e^{1/2}. $$

$\endgroup$
0
$\begingroup$

This solution only assumes $f$ is differentiable at $0$.

Fix $x\ne 0$ and notice that

$$f(x)\left(e^{\frac{x}2} - 1\right) = f\left(2\cdot \frac{x}2\right)\left(e^{\frac{x}2} - 1\right) = f\left(\frac{x}2\right)(e^x-1)$$

so inductively we get

$$f\left(\frac{x}{2^n}\right)(e^x-1) = f(x)\left(e^{\frac{x}{2^n}} - 1\right)$$

Letting $n\to\infty$ and using continuity of $f$ at $0$, we get

$$f(0)(e^x-1) = 0 \implies f(0) = 0$$

Now for $x \ne 0$ we have

$$\frac{f(x)}{e^x-1} = \frac{f\left(\frac{x}{2^n}\right)}{e^{\frac{x}{2^n}}-1} = \frac{f\left(\frac{x}{2^n}\right)}{\frac{x}{2^n}}\frac{\frac{x}{2^n}}{e^{\frac{x}{2^n}}-1} = \frac{f\left(\frac{x}{2^n}\right) - f(0)}{\frac{x}{2^n}}\frac{\frac{x}{2^n}}{e^{\frac{x}{2^n}}-1} \xrightarrow{n\to\infty} f'(0)\cdot1 = 1$$

Therefore $f(x) = e^x-1$ for all $x \ne 0$, and by inspection we also have $f(0) = 1 = e^0-1$.

Hence $f(x) = e^x-1, \forall x \in \mathbb{R}$.

Now the desired limit is

$$\lim_{x\to 0}\left(\frac{f(x)}x\right)^{1/x} = \lim_{x\to 0}\left(\frac{e^x-1}x\right)^{1/x}$$

which can be computed by taking the logarithm and applying l'Hopital thrice:

$$\lim_{x\to 0}\frac{\ln (e^x-1) - \ln x}{x} \stackrel{0/0}= \lim_{x\to 0}\frac{\frac{e^x}{e^x-1} - \frac1x}{1} = \lim_{x\to 0} \frac{xe^x-e^x+1}{x(e^x-1)} \stackrel{0/0}= \lim_{x\to 0}\frac{xe^x+e^x-e^x}{xe^x+e^x-1} = \lim_{x\to 0}\frac{xe^x}{e^x(x+1)} \stackrel{0/0}= \lim_{x\to 0}\frac{xe^x+e^x}{e^x(x+1) + e^x} = \frac{0+1}{1\cdot1 + 1} = \frac12$$

Hence $$\lim_{x\to 0}\left(\frac{e^x-1}x\right)^{1/x} = e^{\lim_{x\to 0}\frac{\ln (e^x-1) - \ln x}{x}} = e^{1/2}$$

$\endgroup$
0
$\begingroup$

Write $\lim_{x \to 0}\left (\frac {f(x)}x \right)^{1/x} =\lim_{x \to 0}\left (\frac {f(2x)}{2x} \right)^{\frac1{2x}} =\lim_{x \to 0}\left (\frac {(e^{2x}-1)f(x)}{(e^{x}-1)2x} \right)^{\frac1{2x}} $

Thus, if $\lim_{x \to 0}\left (\frac {f(x)}x \right)^{1/x}=L$

$ \implies \lim_{x \to 0} \left ( \frac {e^{2x}-1}{2(e^{x}-1)}\right)^{\frac1{2x}}$ $= \sqrt L $

From here it should be easy.

$\endgroup$
  • $\begingroup$ I think you are assuming that the limit exists. $\endgroup$ – Rigel Jun 9 '18 at 17:15
  • $\begingroup$ Yeah! That is a loophole in this proof. $\endgroup$ – Lord KK Jun 9 '18 at 17:26
  • $\begingroup$ I believe it should be $$\lim_{x \to 0}\left (\frac {f(x)}x \right)^{1/x} =\lim_{x \to 0}\left (\frac {f(2x)}{2x} \right)^{\frac1{2x}} =\lim_{x \to 0}\left (\frac {(e^{2x}-1)f(x)}{(e^{x}-1)2x} \right)^{\frac1{2x}} $$ and the limit $$\lim_{x\to0} \left(2\cdot \frac{e^{2x}-1}{e^x-1}\right)^{\frac1{2x}}$$ does not exist. $\endgroup$ – mechanodroid Jun 9 '18 at 17:44
  • $\begingroup$ @mechanodroid Thanks for the correction. Edited. $\endgroup$ – Lord KK Jun 9 '18 at 17:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.